A Hybrid Lightweight System for Early Attack Detection in the IoMT Fog - Hameed, Shilan S; Selamat, Ali; Abdul Latiff, Liza; Razak, Shukor A; Krejcar, Ondrej; Fujita, Hamido; Ahmad Sharif, Mohammad Nazir; Omatu, Sigeru (Sensors (Basel, Switzerland), 2021)
Cyber-attack detection via on-gadget embedded models and cloud systems are widely used for the Internet of Medical Things (IoMT). The former has a limited computation ability, whereas the latter has a long detection time. Fog-based attack detection is alternatively used to overcome these problems. However, the current fog-based systems cannot handle the ever-increasing IoMT's big data. Moreover, they are not lightweight and are designed for network attack detection only. In this work, a hybrid (for host and network) lightweight system is proposed for early attack detection in the IoMT fog. In an adaptive online setting, six different incremental classifiers were implemented, namely a novel Weighted Hoeffding Tree Ensemble (WHTE), Incremental K-Nearest Neighbors (IKNN), Incremental Naïve Bayes (INB), Hoeffding Tree Majority Class (HTMC), Hoeffding Tree Naïve Bayes (HTNB), and Hoeffding Tree Naïve Bayes Adaptive (HTNBA). The system was benchmarked with seven heterogeneous sensors and a NetFlow data infected with nine types of recent attack. The results showed that the proposed system worked well on the lightweight fog devices with ~100% accuracy, a low detection time, and a low memory usage of less than 6 MiB. The single-criteria comparative analysis showed that the WHTE ensemble was more accurate and was less sensitive to the concept drift.
Keywords: Bayesova věta; big data; IoT; časná diagnóza; incremental learning; Internet of Things; Bayes Theorem; fog computing; hybrid attack detection; machine learning; internet věcí; Big Data; Early Diagnosis; IoMT; sensor’s data; NIDS; NetFlow data; HIDS